The Impact of Intellectual Capital, Corporate Social Responsibility, and Non Performing Financing on Company Value - Siti Fatimah; Abdul Rahman; Nurjannah (International Journal of Islamic and Social Sciences (ISOS), 2021)
This study aims to examine the impact of Intellectual Capital (IC), Corporate Social Responsibility (CSR), as well as Non Performing Financing (NPF), on the value of the company with Good Corporate Governance (GCG) as a moderating variable. The object of this research is a commercial bank sharia in Indonesia in 2011-2019, with a sample of 5 sharia commercial banks. Which method used in the sample selection is purposive sampling. The data used in the form of data secondary sources derived from the annual report and good corporate governance reports, while the technical the data analysis used is multiple regression analysis and moderating regression analysis. The results of this study indicate that intellectual capital and non-performing financing negative and insignificant effect on firm value, corporate social responsibility positive and significant effect on firm value, good corporate governance does not able to moderate the relationship between intellectual capital and non-performing financing to corporate value, good corporate governance is able to strengthen the relationship between corporate social responsibility for the value of the company.